Effect of Adjuvant (Hormonal) Therapy on Bone Mineral Density in Caucasian Women with Breast Cancer - Khachidze, Nana; Giorgadze, Elene; Tsagareli, Marina; Dolidze, Nino; Sulikashvvili, Tea (European Scientific Journal, ESJ, 2017)
Background and Aim: Aromatase inhibitors (AIs) and selective estrogen receptor modulators (SERMs) are important components of adjuvant endocrine therapy in postmenopausal women with estrogen receptor positive breast cancer. The aim of our study was to assess the effect of AIs and SERMs on bone mineral density (BMD) in Caucasian postmenopausal women with breast cancer. Patients and Methods: 118 postmenopausal Caucasian women were enrolled in the study. 60 patients were receiving AIs and 58 patients – SERMs-Tamoxifen. Patients were also divided into two sub groups: 1) patients with more than 3 years of last menstrual period (LMP) and 2) patients with less than 3 years of last menstrual period. Results: Among Aromatase inhibitors treated patients, there was a decrease in median BMD from baseline to 5 years in lumbar spine and total hip compared with the Tamoxifen group. No patients with normal BMD at baseline became osteoporotic at 5 years. Conclusion: Aromatase inhibitors are associated with accelerated bone loss over the 5-year treatment period. In postmenopausal women, treatment with tamoxifen is associated with preservation of the bone mineral density of the lumbar spine.